Glacier and glacier hazard characterization based on remote sensing interpretation: a case study in Qinghai Province, China - Li, Delin; Li, Zongren; Guan, Peng; Huang, Li; Wei, Sailajia; Li, Qiping; Qi, Huijun; Zhang, Xing; Kong, Decai; Ma, Shibin; Hou, Yonghao; Li, Zibin; et al. (Frontiers in Earth Science, 2025)
Against the backdrop of global climate warming, glaciers across the Qinghai–Tibet Plateau are undergoing widespread retreat, glacial lakes are expanding rapidly, and disasters such as ice avalanches and glacial lake outburst floods (GLOFs) are occurring with increasing frequency, posing severe threats to regional transportation arteries, energy facilities, and urban safety. As a typical concentration area of glaciers and glacier-related hazards, Qinghai Province holds great scientific and engineering significance for related research. By integrating medium- and high-resolution optical imagery, SAR data, InSAR techniques, and field investigation records, this study systematically extracted glacier extent, glacial lake evolution, glacier surface velocity, and mass balance variations in Qinghai Province. Results reveal that between 2000 and 2020, the province’s glaciers retreated by approximately 230.49 km2, with the most significant shrinkage occurring within the 5,300–5,500 m elevation range. A threefold classification system for ice avalanche hazards, applicable to the Qinghai-Tibet Plateau, is proposed, which includes direct ice avalanche hazards, ice avalanche-glacial lake outburst hazards, and ice avalanche-dammed lake chain hazards. A total of 551 glacier-related geohazard sites were identified in Qinghai Province, primarily concentrated in the Kunlun and Tanggula Mountains. Based on the engineering geological analogy method and a multi-factor weighted overlay approach, a glacier hazard susceptibility assessment system was constructed, dividing the study area into low, medium, and high susceptibility zones. The findings not only deepen the understanding of glacier-climate-hazard coupling mechanisms but also provide a scientific basis for regional disaster prevention, mitigation, and the operational safety of major infrastructure projects.